2011
DOI: 10.1007/s00264-011-1321-8
|View full text |Cite
|
Sign up to set email alerts
|

Negative pressure wound therapy to prevent seromas and treat surgical incisions after total hip arthroplasty

Abstract: NPWT has been used on many different types of traumatic and non traumatic wounds. This prospective, randomised study has demonstrated decreased development of postoperative seromas in the wound and improved wound healing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
173
2
7

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 191 publications
(191 citation statements)
references
References 17 publications
(24 reference statements)
6
173
2
7
Order By: Relevance
“…After removal of duplicates, 872 remained. Eighty‐three full‐text papers were retrieved for inspection, of which seven were RCTs33, 34, 35, 36, 37, 38, 39. A further six unpublished studies were identified through contact with manufacturers and by searching ClinicalTrials.gov.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…After removal of duplicates, 872 remained. Eighty‐three full‐text papers were retrieved for inspection, of which seven were RCTs33, 34, 35, 36, 37, 38, 39. A further six unpublished studies were identified through contact with manufacturers and by searching ClinicalTrials.gov.…”
Section: Resultsmentioning
confidence: 99%
“…(personal communication), used an NPWT device (VAC®) and six34, 35, 38, 39, including those of S. Karlakki et al . and R. Galiano et al .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations